Manual de estrategias pedagógicas diversificadas para el abordaje de la comunicación oral en niños con síndrome down en nivel de educación parvularia - Oyarzo Velásquez, Ximena (Ariadna Ediciones, 2022)
The Manual of Diversified Pedagogical Strategies to address the development of Language in children with Down Syndrome (DS) at the Early Childhood Education level, arises from the need to make visible the inclusive educational policies implemented by the Ministry of Education. The development of the manual originates from the final reflection of the Graduation Seminar of the School of Pedagogy in Differential Education with a mention in Hearing and Language and Intellectual Disability of the Austral University of Chile, Puerto Montt Campus, year 2020.